The development of the evidence-based SDM(MCC) intervention to improve shared decision making in geriatric outpatients: the DICO study - Pel-Littel, Ruth E. (BMC Med Inform Decis Mak, 2020)
BACKGROUND: Shared decision making (SDM) contributes to personalized decisions that fit the personal preferences of patients when choosing a treatment for a condition. However, older adults frequently face multiple chronic conditions (MCC). Therefore, implementing SDM requires special features. The aim of this paper is to describe the development of an intervention to improve SDM in older adults with MCC. METHODS: Following the Medical Research Council framework for developing complex interventions, the SDM(MCC) intervention was developed step-wise. Based on a literature review and empirical research in a co-creation process with end users, we developed training for geriatricians and a preparatory tool for older patients with MCC and informal caregivers. After assessing feasibility, the intervention was implemented in a pilot study (N = 108) in two outpatient geriatric clinics of an academic and a non-academic teaching hospital in Amsterdam, the Netherlands. RESULTS: Key elements of the training for geriatricians include developing skills to involve older adults with MCC and informal caregivers in SDM and following the six-step ‘Dynamic model for SDM with frail older patients’, as well as learning how to explore personal goals related to quality of life and how to form a partnership with the patient and the informal caregiver. Key elements of the preparatory tool for patients include an explicit invitation to participate in SDM, nomination that the patient’s own knowledge is valuable, invitation to form a partnership with the geriatrician, encouragement to share information about daily and social functioning and exploration of possible goals. Furthermore, the invitation of informal caregivers to share their concerns was also a key element. CONCLUSIONS: Through a process of co-creation, both training for geriatricians and a preparatory tool for older adults and their informal caregivers were developed, tailored to the needs of the end users and based on the ‘Dynamic model of SDM with frail older patients’.